Sensor based sustainable wastewater management in chrysanthemum (Chrysanthemum morifolium Ramat.) under climate change for enhanced productivity - ANKIT; DOLMA, DEACHEN; GURJAR, D S; JAIN, RITU (Journal of Ornamental Horticulture, 2025)
Water is well-thought-out as the most precarious resource for sustainable development. Diversion of high volume of freshwater to other commercial and industrial sectors due to rapid increase in industrial activities resulted into generation of huge quantity of wastewater. Crops like cut flowers having un-edible economic parts is proposed to be the most feasible and remunerative option with wastewater irrigation. Sensor based wastewater application in cut flowers has the potential to enhance both water use efficiency and water use. Keeping with this objective, a field study was conducted with four replications and six treatments viz. T1: Irrigation with groundwater scheduled at 25% MAD, T2: Irrigation with groundwater scheduled at 50% MAD, T3: Irrigation with groundwater scheduled at 75% MAD, T4: Irrigation with wastewater scheduled at 25% MAD, T5: Irrigation with wastewater scheduled at 50% MAD, T6: Irrigation with wastewater scheduled at 75% MAD in randomized block design (RBD). A soil indicator based approach (MAD) is used as a criteria for scheduling irrigation. Three levels of MAD (25, 50 and 75%) values were quantified by Frequency Domain Reflectrometry (FDR) soil moisture sensor. For each plot (2.25 m2) the amount of water to be applied at each depletion point was calculated by area of plot and irrigation water depth/ Refill amount. The study compared different flowering, yield and biochemical attributes of chrysanthemum. Results from the above statistically analyzed data found that all the flowering, yields and biochemical attributes were found significantly higher in T5 i.e. Irrigation with wastewater scheduled at 50% MAD compared to other groundwater and wastewater irrigated treatment. Generally chrysanthemum crop is responsive to application of nutrients at optimum soil moisture levels. At last it can be concluded that sensor based wastewater application in chrysanthemum at 50% MAD significantly increased flowering, yield and biochemical characteristics. Hence in chrysanthemum 50% MAD value is optimum for irrigation.